Two Case Reports of Life-Threatening Ethanol-Induced Anaphylaxis - S.L. Fernando; L.R. Clarke (Karger Publishers, 2009)
Adverse reactions to alcoholic beverages are common and diverse in aetiology. Ethanol-induced anaphylaxis, however, is a rare but often life-threatening condition that warrants careful evaluation in suspected individuals. We present the cases of two patients who developed urticaria, angioedema and throat constriction within minutes of consuming white wine. Both individuals demonstrated no adverse reaction to double-blind placebo-controlled challenges to metabisulphite or sodium salicylate. However, an open challenge to white wine elicited urticaria in both subjects. This reaction was reproduced with a double-blind placebo-controlled challenge to ethanol and was accompanied by a rise in serum total tryptase levels. Positive skin test responses to 2% acetic acid, a breakdown product of ethanol, were elicited from both patients but not from three normal controls. These two cases demonstrate the need for a systematic approach for the evaluation of allergic reactions to alcohol.